The Role of Physical Activity in Male Reproductive Health – A Systematic Review - Prus, Joanna; Łuczak, Klaudia; Sitarek, Hanna; Tabeau, Adrianna; Dudek, Patryk; Ulicka, Wiktoria; Chudzikowski, Marcel; Pięta, Justyna; Pawlik, Agnieszka; Prokopiuk, Agata (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Nowadays infertility is an important problem, which affects even 17,5% couples during their lifetime. There are many factors playing a role in the development of infertility, among others the ones connected with lifestyle. There are many studies analysing lifestyle influence on the male reproductive health. The aim of this article is to review available literature concerning physical activity and to analyse its impact on male fertility, considering different exercise-related mechanisms, which may cause impairments. Materials and Methods: The literature review was conducted via PubMed database and the search terms were as follows: “physical activity”, “sport”, “male fertility” and “male infertility”. We included only the articles written in English and the search was limited to the following types of articles: clinical trials, meta-analyses, systematic reviews and reviews. The studies cited in the mentioned reviews were also included. State of knowledge: Physical activity affects male reproductive health on both ways – moderate exercise has a positive effect on male fertility, while an extent activity impairs it. The negative effect is caused by many mechanisms, such as impairing the functioning of hormonal axes, worsening semen parameters or injuries causing urogenital disorders. Conclusions: People, particularly men with lifestyle-induced infertility issues, should be enhanced to sport. It is important to maintain an appropriate, moderate level of physical activity though. Further research in this field is still needed, because of the importance and prevalence of the infertility question.